Use of head-mounted display technology to support teaching through virtual learning environments in non-formal contexts - De Simone, Giuseppe; Di Tore, Stefano; Maffei, Sara; Sibilio, Maurizio; Todino, Michele Domenico (ITALIAN JOURNAL OF EDUCATIONAL RESEARCH, 2017)
COM (International Council of Museum) defines a museum as a permanent institution in the service of society and its development, open to the public, which acquires, conserves, researches, communicates and exhibits the tangible and intangible heritage of humanity and its environment for the purposes of education, study and enjoyment. This statement seems to emphasize how a museum can be an education institution that embedded an educational project. Considering this (and reminding a progressive introduction of protocols and agreements between the Italian Ministry of Education, University and Research (MIUR) and national, regional as well as provincial museums), in 2015 the Department of Humanities, Philosophy and Education of the University of Salerno (DISUFF) and the Virtual Archaeological Museum of Herculaneum (MAV) signed a scientific cooperation agreement oriented to develop and implement methods, tools and inclusive educational technologies. The first project, of this cooperation, consists in the realization of an Edugame, usable through the virtual reality Oculus Rift technology (one of the types of headmounted display present on the market) set inside the MAV 3D model of Villa of the Papyri in Herculaneum. The game is realized to be explorative and interactive, that link the Italian archeological museums systems and didactic necessity to improve the teaching-learning process for the users of the Edugame. In this regard, the use of head-mounted display technologies, can offer a good support to teaching-learning process due to virtual learning environments in non-formal contexts.